Controls Over Oxygen Isotope Fractionation in the Waters and Bivalves (Arthritica helmsi) of an Estuarine Lagoon System. (3rd June 2021) - Chamberlayne, B. K.; Tyler, J. J.; Gillanders, B. M.
Abstract: Oxygen isotope ratios in bivalve shells have long been used as a proxy for environmental change, reflecting both temperature and the oxygen isotope composition of host water. In estuarine systems, the oxygen isotope composition of water is complicated by variable mixing between river and seawater, as well as evaporative enrichment. In addition, due to species‐specific variation in temperature‐dependent fractionation into bivalve carbonate, modern calibrations are necessary prior to applications in paleoenvironmental studies. In this study, live specimens of the micromollusc Arthritica helmsi were collected from five sites in the Coorong Lagoon, an estuarine system at the mouth of the River Murray, Australia, on six occasions from November 2016 to May 2018. Whole shell oxygen and carbon isotope compositions ( n  = 131) were measured alongside monthly temperature and oxygen and hydrogen isotope analyses of waters from the Coorong and neighboring Lake Alexandrina ( n  = 137). Oxygen and hydrogen isotope ratios in water were mostly controlled by evaporation of source waters, though a period of high river water discharge was reflected in the isotopic values of the Coorong North Lagoon. A species‐specific temperature‐dependent oxygen isotope fractionation equation was calibrated for A. helmsi : T (°C) = (21.39 ± 0.45) − (4.43 ± 0.38) × (δ 18 Oshell  − δ 18 Owater ). This equation is similar to other published paleotemperature equations for biogenic carbonates. These contemporary observations of the isotope hydrology of the Coorong, coupled with our contemporary calibration of oxygen isotope fractionation, lay the foundation for paleoenvironmental studies using bivalves collected from the sediments of the Coorong. Key Points: Oxygen and hydrogen isotope ratios in waters of the Coorong Lagoons are mostly controlled by evaporation A new temperature‐dependent oxygen isotope fractionation equation for Arthritica helmsi is developed Fossil shells of A. helmsi are suitable for paleoenvironmental studies